2023
DOI: 10.3390/ma16247651
|View full text |Cite
|
Sign up to set email alerts
|

Application of Industrial Waste Materials by Alkaline Activation for Use as Geopolymer Binders

Kinga Setlak,
Janusz Mikuła,
Michał Łach

Abstract: The purpose of this study is to synthesize geopolymer binders as an environmentally friendly alternative to conventional cement using available local raw materials. Waste materials such as chalcedonite (Ch), amphibolite (A), fly ash from lignite combustion (PB), and diatomite dust (D) calcined at 900 °C were used to produce geopolymer binders. Metakaolin (M) was used as an additional modifier for binders based on waste materials. The base materials were subjected to fluorescence X-ray fluorescence (XRF) analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…The most common alkali activators are sodium hydroxide (NaOH) and sodium silicate (Na 2 SiO 3 , water glass) [32,33]. It is suggested that for alkali-activated slag cementitious materials, sodium silicate should be used [34,35], taking into consideration factors such as the molar concentration, the solution-binder ratio (s/b), and alkalinity [32,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The most common alkali activators are sodium hydroxide (NaOH) and sodium silicate (Na 2 SiO 3 , water glass) [32,33]. It is suggested that for alkali-activated slag cementitious materials, sodium silicate should be used [34,35], taking into consideration factors such as the molar concentration, the solution-binder ratio (s/b), and alkalinity [32,36,37].…”
Section: Introductionmentioning
confidence: 99%